Sound, mobility and landscapes of exhibition: radio-guided tours at the Science Museum, London, 1960–1964. (April 2016) - Rich, Jennifer
Abstract: From 1960 to 1964 the Science Museum in London experimented with the technique of audio guide known as the radio-guided tour. The scheme formed part of a Museum-wide initiative dedicated to the education of the 'average visitor': a growing body of the museum-going public with a popular interest in science and technology. This paper positions the radio-guided tour within a period of rapid development at the Science Museum characterised by the reconfiguration of its landscapes of exhibition. It shows how the radio-guided tour helped to navigate new techniques of exhibition display, particularly that known as 'exhibition as landscape', which aimed to cultivate the appropriate sets of emotion necessary for an appreciation of, and, importantly, a feeling for, science and its applications in technology. The paper contributes to literature on the sonic and mobile makings of landscape, in particular that which has called for a critical phenomenological approach concerned with the social, cultural and political dimensions of embodied engagements with landscape practice. It also contributes to recent museum studies literature with its foregrounding of the body and the sensorium in the configuration of the spaces of knowledge at the museum. Highlights: Argues that 'exhibition as landscape' played a central role in the Science Museum's post-war redevelopment. Demonstrates how sound and mobility helped to shape new exhibition landscapes. Traces the role of visitor participation in developing a feeling for science as active citizenship. Takes a critical phenomenological approach to sound and landscape.